2014
DOI: 10.1093/eurheartj/ehu053
|View full text |Cite
|
Sign up to set email alerts
|

Coronary computed tomography angiography with model-based iterative reconstruction using a radiation exposure similar to chest X-ray examination

Abstract: AimsTo evaluate the feasibility and image quality of coronary computed tomography angiography (CCTA) acquisition with a submillisievert fraction of effective radiation dose using model-based iterative reconstruction (MBIR) for noise reduction.Methods and resultsIn 42 patients undergoing standard low-dose (100–120 kV; 450–700 mA) and additional ultra-low-dose CCTA (80–100 kV; 150–210 mA) reconstructed with MBIR, segmental image quality was graded on a four-point scale [(i): non-evaluative, (ii): good, (iii): ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…One study found an ultra-low dose of 0.2 mSv in patients with a mean BMI of 25.2 kg m 22 using Model-Based Iterative Reconstruction, which is a modelbased IR algorithm. 22 All other studies investigated less advanced hybrid IR algorithms. Therefore with the development of model-based IR algorithms, the radiation dose is expected to decrease even further.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One study found an ultra-low dose of 0.2 mSv in patients with a mean BMI of 25.2 kg m 22 using Model-Based Iterative Reconstruction, which is a modelbased IR algorithm. 22 All other studies investigated less advanced hybrid IR algorithms. Therefore with the development of model-based IR algorithms, the radiation dose is expected to decrease even further.…”
Section: Discussionmentioning
confidence: 99%
“…This explains why only two studies performed additional scans for research purposes in the same patients. 18,22 Another study tried to simulate a withinpatient comparison by using data from one detector of a dual source CT system. 20 This meta-analysis provides the possible dose reduction with IR as reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the traditional reconstruction technique (filtered back projection [FBP]), radiation-dose reduction causes an increase in the image noise. However, iterative reconstruction (IR) techniques have been shown to reduce image noise and radiation dose and improve image quality [17,18]. Low tube voltage together with low-concentration contrast agent have been increasingly used in recent years, but most studies have focused on coronary arteries, head and neck, and pulmonary arteries [17,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%